2015
DOI: 10.3390/ijerph120808861
|View full text |Cite
|
Sign up to set email alerts
|

School Term vs. School Holiday: Associations with Children’s Physical Activity, Screen-Time, Diet and Sleep

Abstract: This cross-sectional study examined differences in children’s health behaviors during school term (ST) versus school holiday (SH: June–July) and how associations changed when weather characteristics were considered. Children aged 5–18 years (n = 406) from a subtropical climate reported behaviors over 20 months. Multivariable regression models controlling for age, sex, race and body mass index z-score(BMIz ) were used to examine associations between SH and each behavior. A second model included heat index, prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 12 publications
3
37
4
Order By: Relevance
“…A previous study reported similar associations between higher temperatures and ACS in children. Higher total precipitation was slightly associated with ACS choice in children, a different finding given the associations previously seen between rainfall and physical activity in general . Moreover, in a qualitative study, older adolescents reported to prefer the use of motorized transportation in rainfall conditions, but we found no association in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous study reported similar associations between higher temperatures and ACS in children. Higher total precipitation was slightly associated with ACS choice in children, a different finding given the associations previously seen between rainfall and physical activity in general . Moreover, in a qualitative study, older adolescents reported to prefer the use of motorized transportation in rainfall conditions, but we found no association in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher total precipitation was slightly associated with ACS choice in children, a different finding given the associations previously seen between rainfall and physical activity in general. [26][27][28][29][30] Moreover, in a qualitative study, older adolescents reported to prefer the use of motorized transportation in rainfall conditions, 17 but we found no association in the current study. This difference might be explained by the methodology used, with the qualitative study reporting the intention of the adolescents for commuting given different rainfall conditions, while our study follows a quantitative methodology which showed how the adolescents actually commuted regardless of their preferences.…”
Section: Discussioncontrasting
confidence: 84%
“…Currently, only a handful of studies have examined differences in children's obesogenic behaviors during summer versus school . One cross‐sectional study reported children were more physically active and had higher TV viewing during school holidays compared to school, with no reported dietary or sleep differences .…”
mentioning
confidence: 99%
“…Currently, only a handful of studies have examined differences in children's obesogenic behaviors during summer versus school . One cross‐sectional study reported children were more physically active and had higher TV viewing during school holidays compared to school, with no reported dietary or sleep differences . An analysis of secondary data of US children from the National Health and Nutrition Examination Survey (NHANES 2003‐2008) reported children were more active, had less healthful diets, and watched more television during school breaks compared to school .…”
mentioning
confidence: 99%
See 1 more Smart Citation